Long-period magnetic disturbances or Pc5 events aboard INTERBALL-Auroral and POLAR - Bochev, A.; Nenovski, P.; Lakhina, G.S.; Sinha, Ashwini K. (Advances in Space Research, v.37/3, p.592-598, 2006, doi: 10.1016/j.asr.2005.09.012, 2006)
This paper discusses observations of dynamic magnetic field variations on auroral field lines at mid and high altitudes, utilizing a conjunction of POLAR and INTERBALL-Auroral spacecraft in the dusk magnetosphere on January 11, 1997. Both spacecraft indicate the presence of periodic magnetic variations in the Pc5 frequency range in the field-aligned current region 1. The satellites are believed to be closely on the same field line or within a flux tube (radius 130 km of its projection in the ionosphere). The polarization analysis shows an interesting event: a rotation of the main polarization axis by about 90° between POLAR and INTERBALL. When the two spacecraft are very close to a common field line, the difference between their observed magnetic fields might arise from a rotation of the field between the two altitudes. We cannot exclude different polarization properties arising from different horizontal positions (although small) of both satellite with respect to local plasma boundary. Frequency analysis of both solar wind density (WIND) and INTERBALL magnetic field showed that the solar wind pressure variation contains the same spectrum (2.4–4.4 mHz). It appears that the solar wind pressure variations are sufficient for a parametric mechanism of excitation of compressional disturbances propagating along the magnetopause and within the magnetospheric cavity.
Keywords: ULF waves; Magnetospheric dynamics; Satellite conjunction; POLAR; INTERBALL-Auroral; Solar wind